If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(t+3)9=3(t+2)+6
We move all terms to the left:
5(t+3)9-(3(t+2)+6)=0
We multiply parentheses
45t-(3(t+2)+6)+135=0
We calculate terms in parentheses: -(3(t+2)+6), so:We get rid of parentheses
3(t+2)+6
We multiply parentheses
3t+6+6
We add all the numbers together, and all the variables
3t+12
Back to the equation:
-(3t+12)
45t-3t-12+135=0
We add all the numbers together, and all the variables
42t+123=0
We move all terms containing t to the left, all other terms to the right
42t=-123
t=-123/42
t=-2+13/14
| 3a−24= 9 | | -6s=-10s+8 | | -10-n=10+5n+10 | | 4h−3=33 | | 11xX2=73 | | 4x-8=2(x+2)+2x-10* | | -9-4+7x=4-6x | | 2(1x-5)=20 | | 15+10=-5(7x-5) | | 60+50.45=57.95b | | 5/6=1/6d | | 5(a+4)-6a+1=15 | | 4(-8x+3)=12-32x | | 8/a=10/8 | | c3=2 | | 3x-7=97 | | 2x(2x^2+17x+21)=0 | | -x+18=2x | | -10+2p=-4+p | | -143=11(1+2x) | | 6/4c=-10 | | 8x+38=–3(–6–4x) | | 4b+1-b=10 | | r/3+-28=-4 | | 0.75(x+40)=0.35(x+20+0.35(x-20) | | 3a+7+5-4=0 | | 12+x-5=25-5 | | {1}{2}(p+2)=-3-p | | 6x+3(4x-2=5(2x-8) | | -2k=-k-10 | | 10x+8=-68 | | 1/3(27x+18)=12+6(x−4) |